Issues and Impact of Lean Construction Implementation in The Malaysian Construction Industry - MARHANI, MOHD ARIF; Muhammad Othman, Nurul Ain Syafiqah; Ismail, Noor Akmal Adillah (International Journal of Sustainable Construction Engineering and Technology, 2021)
The construction industry is one of the most important industries because of its end product, such as schools, hospitals, and roads. This industry contributes to social and economic development by providing buildings for other sectors’ usage. Nevertheless, despite these contributions, the construction industry also has issues related to construction wastes, which need to be resolved. Hence, Lean Construction (LC) approach is a useful technique that traditionally converged on minimizing construction waste. LC is an approach based on lean production that emphasizes minimally invasive and maximally profitable production. This paper’s primary purpose is to explore the usage of LC in the Malaysian construction industry (MCI). This paper aims to identify LC implementation issues, determine the impact of LC implementation, and recommend enhancing the LC implementation in the MCI. Data was obtained from G7 contractors registered with the Construction Industry Development Board of Malaysia (CIDB) by distributing questionnaire surveys, and the response rate was 20%. Through the descriptive analysis, it can be concluded that most of the respondents agreed with lack of knowledge was the major issue that occurred during the LC implementation in the MCI. Furthermore, the respondents agreed that LC positively impacted the LC practitioners’ organization by encouraging them to undertake construction materials appropriately without wasting them and improving handling the site’s resources. Based on the findings, it is recommended that the government should introduce this LC as a policy in managing a construction site, and LC practitioners should implement the best construction practices to obtain the best results. Additionally, it is also suggested that the industry educate the construction workforce on implementing this LC concept and create more ongoing seminars or training to upgrade their knowledge, skills, techniques, and processes. This research’s outcomes play an essential role in reducing the gap between the theory and implementation practices of LC in the MCI. Thus, this LC is hoped that future construction projects in the MCI can produce a better quality of end products towards a better quality of life.